PENGARUH RELIGIUSITAS TERHADAP RESIDIVISME PADA RUTAN KELAS IIA YOGYAKARTA - Raden Muhamad Haikal Yasin; Padmono Wibowo (Jurnal Komunikasi Hukum, 2024)
The penitentiary system in Indonesia has an important role in coaching prisoners to restore their lives and reduce recidivism rates. However, high recidivism rates indicate problems in the effectiveness of coaching, with many inmates reoffending after release. This research aims to examine the influence of religiosity on recidivism in the Class IIA Yogyakarta Detention Center. The research method used was descriptive quantitative, with a sample consisting of 40 recidivist prisoners who were analyzed using simple linear regression. The research results show that the levels of religiosity and recidivism are in the medium category, which indicates the potential for interaction between the two. Further analysis shows that there is a significant positive influence between religiosity and recidivism, with a calculated t value of 3.467, greater than the t table, which means that the higher the religiosity, the greater the possibility of recidivism increasing. Regression tests show that religiosity contributes 24% to the variation in recidivism.